La imagen corporativa del Hospital Provincial General Docente Riobamba y su incidencia en el usuario externo. - Lluguín Valdiviezo, Elizabeth (2016)
Corporate Image Provincial General Teaching Hospital of Riobamba and its impact on the External User. In the country it has been observed that the health sector is in the periodic table for discussion. This situation leads us to have a growing interest in this sector. This is how, in this research the topic of Corporate Image Riobamba Provincial General Teaching Hospital and its impact on the external user addresses. The Provincial General Teaching Hospital Riobamba is one of the main health institutions with which the city of Riobamba. It employs 728 workers and employees. Managing their internal communication under the Department of Communication and Press that carries out concrete actions for the user, as in the case of corporate values, with which it is intended that the members are experts, welcoming, supportive of the public who come to this house of health. The purpose of this work was the preparation of a Corporate Identity Manual, as it constitutes one of the most important (intangible) assets of the institution generate added value and differentiating it from other nursing homes. Among its objectives, the incidence of the corporate image in the access to the hospital were found, which gave us the understanding and implementation of strategies in order to communicate the values we want to highlight. The research part of a conceptual vision of the existing theory to the framework to approach the object of study by a scientific methodology. As a next step data were collected through quantitative techniques audit surveys consistent image in this house people attending health and qualitative techniques such as content analysis, this was done in order to make a diagnosis of the situation regarding the corporate image of the institution. These tools were very useful to us giving us information needed for the development of this research. In conclusion we can say that clearly demonstrates the need for innovation of a manual on corporate image, to improve its position in the citizenship and thus improve customer chimboracense user.